PENGEMBANGAN INSTRUMEN KETERAMPILAN PROSES SAINS DENGAN DESAIN PEMBELAJARAN BERDIFERENSIASI DI TINGKAT SEKOLAH DASAR - Siti Aisah; Ria Rizki Agustini (Institut Pendidikan Tapanuli Selatan, 2024)
Science process skills, such as scientific procedures in science learning, are able to deepen students' mastery of a concept. This development research is based on the need for an assessment instrument to measure science process skills (KPS). So far, assessments still emphasize science as a product or knowledge. This research using the R&D method, uses a 4D instrument development model. At the definition stage, initial-finish analysis, student analysis, formulation of concepts, and learning objectives are carried out. The design stage is carried out by compiling test criteria, selecting formats, and creating instrument grids. At the development stage, the results of the feasibility test from the validator obtained an average value of 88%, which means the instrument is very feasible. The instrument was then revised based on validator input and suggestions. The revised instrument was tested on a large group. Trials on 190 students produced 37 valid questions out of 40 questions with a reliability value of 0.745, meaning that the assessment instrument is suitable for use as a tool to measure students' science process skills. Keywords: development of assessment instruments, science process skills, and science learning